2020
DOI: 10.1098/rsob.190228
|View full text |Cite
|
Sign up to set email alerts
|

DNA topoisomerase IIIβ promotes cyst generation by inducing cyst wall protein gene expression in Giardia lamblia

Abstract: Giardia lamblia causes waterborne diarrhoea by transmission of infective cysts. Three cyst wall proteins are highly expressed in a concerted manner during encystation of trophozoites into cysts. However, their gene regulatory mechanism is still largely unknown. DNA topoisomerases control topological homeostasis of genomic DNA during replication, transcription and chromosome segregation. They are involved in a variety of cellular processes including cell cycle, cell proliferation and differentiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 73 publications
0
31
0
1
Order By: Relevance
“…We have developed a CRISPR/Cas9 system to successfully disrupt the mlf and top3β genes [ 44 , 57 ]. We further used this system for the targeted disruption of the mbf1 gene.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have developed a CRISPR/Cas9 system to successfully disrupt the mlf and top3β genes [ 44 , 57 ]. We further used this system for the targeted disruption of the mbf1 gene.…”
Section: Resultsmentioning
confidence: 99%
“…We confirmed the replacement of the mbf1 gene with the puromycin acetyltransferase (pac) gene by PCR and sequencing analysis of genomic DNA ( Figure 8 B,C and Figure S6 ), and found a successful disruption of the mbf1 gene by about 29% and a partial replacement of the mbf1 gene with the pac gene ( Figure 8 B,C). G418, an inhibitor of polypeptide synthesis, had cytotoxicity and was used to test the drug sensitivity of the top3β targeted disruption cell line [ 57 ]. We also used G418 to test the drug sensitivity of the MBF1td cell line and found that the viability of the MBF1td cell line decreased compared to the control cell line after G418 treatment, suggesting that MBF1td cell line exhibited increased sensitivity to G418 ( Figure 8 D).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations